Impact of Direct-Acting Antivirals on the Burden of HCV Infection Among Persons Who Inject Drugs and Men Who Have Sex With Men in the Swiss HIV Cohort Study. (26th June 2018) - Salazar-Vizcaya, Luisa; Wandeler, Gilles; Fehr, Jan; Braun, Dominique; Cavassini, Matthias; Stoeckle, Marcel; Bernasconi, Enos; Hoffmann, Matthias; Rougemont, Mathieu; Béguelin, Charles; Rauch, Andri; ,
Abstract: In the Swiss HIV Cohort Study, the number of people who inject drugs with replicating hepatitis C virus (HCV) infection decreased substantially after the introduction of direct-acting antivirals (DAAs). Among men who have sex with men, the increase in DAA uptake and efficacy was counterbalanced by frequent incident HCV infections.